2014
DOI: 10.1504/aajfa.2014.059501
|View full text |Cite
|
Sign up to set email alerts
|

The effects of second language on ethical judgement in accounting

Abstract: The number of participants in accounting practices and academia who use English as their second language is significant and growing. Many of them are involved in making ethical judgements based on information provided in English, which is their second language. It is important to know the effect of the second language on their ethical judgement. In this study, using 211 undergraduate accounting students whose native language is Arabic from an Association to Advance Collegiate Schools of Business (AACSB) accred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Srinidhi et al , 2011; Abbott et al , 2012; García-Sánchez et al , 2017; Ain Qurat et al , 2020; Sultana et al , 2020) and language (e.g. Saadullah et al , 2014; Evans, 2018; Liguori and Steccolini, 2018). These cultural factors explain managers' and directors' behaviors, and consequently the content of accounting information.…”
Section: Background Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Srinidhi et al , 2011; Abbott et al , 2012; García-Sánchez et al , 2017; Ain Qurat et al , 2020; Sultana et al , 2020) and language (e.g. Saadullah et al , 2014; Evans, 2018; Liguori and Steccolini, 2018). These cultural factors explain managers' and directors' behaviors, and consequently the content of accounting information.…”
Section: Background Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Certain sounds in each of the languages are absent in the other one; for example there is no equivalent for the letter 'p' or 'v' in Arabic and there are no equivalents for the letters ‫,غ‬ ‫,ع‬ ‫,ﻕ‬ ‫,ﺥ‬ or ‫ث‬ in English. Moreover, Saadullah et al (2014) found that Arabic-speaking individuals' ethical judgment and decision-making are significantly better when ethical dilemmas are presented to them in Arabic compared to when the same dilemmas are presented in English. This may also be true in situations where the participants in a research study are completing an instrument in their second language, which would seriously affect the validity of the findings of any such study.…”
mentioning
confidence: 97%